(3eLghdGJ bSi GdcQIs - (3eMeO Hf eYGO GdKYHGjfj, CHh YHO Gddgs
(3ChdgG (B:s
(3fQjO Cf fHjf ai gPG GdcJGH GSJNQGL ebGOjQ GdbSi GdhGbYI Ydi XgQ GdcQI , heYQaI GdRhGjG s
(3BNQgG (B:s
(3aEPG YdeJ GdeSCdJjf YdefG cd eKdK Cda HGA Lje Ch Cda HGA RGi hPdc eGCQOfG Cf GHjf (B( (3cPG (B) (3ced GdcJGH hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B22s
(3ajgG QShe gfOSjI eJbfI hLOGhds
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs